Respuesta :
Part a) [tex]-\frac{1}{2} +\frac{1}{3}[/tex]
[tex]-\frac{1}{2} +\frac{1}{3}=\frac{-3+2}{(3*2)} =-\frac{1}{6}[/tex]
the answer Part a) is
[tex]-\frac{1}{6}[/tex]
Part b) [tex]-3\frac{1}{5} +(-6\frac{1}{2} )[/tex]
we know that
[tex]-3\frac{1}{5}=-\frac{3*5+1}{5}=- \frac{16}{5}[/tex]
[tex]-6\frac{1}{2}=-\frac{6*2+1}{2}=- \frac{13}{2}[/tex]
substitute
[tex]- \frac{16}{5}-\frac{13}{2}=\frac{-32-65}{10} =-\frac{97}{10}[/tex]
therefore
the answer part b) is
[tex]-\frac{97}{10}[/tex]
Part c) [tex]\frac{5}{8}-(- \frac{2}{8})[/tex]
[tex]\frac{5}{8}-(- \frac{2}{8})=\frac{5}{8}+ \frac{2}{8}=\frac{7}{8}[/tex]
therefore
the answer part c) is
[tex]\frac{7}{8}[/tex]
Part d) [tex]-\frac{9}{10}- \frac{2}{5}[/tex]
[tex]-\frac{9}{10}- \frac{2}{5} =\frac{-9-4}{10}=- \frac{13}{10}[/tex]
therefore
the answer part d) is
[tex]- \frac{13}{10}[/tex]
Part e) [tex]6\frac{3}{5}-(2\frac{1}{5})[/tex]
we know that
[tex]6\frac{3}{5}=\frac{6*5+3}{5}=\frac{33}{5}[/tex]
[tex]2\frac{1}{5}=\frac{2*5+1}{5}=\frac{11}{5}[/tex]
substitute
[tex]\frac{33}{5}-\frac{11}{5}=\frac{22}{5}[/tex]
therefore
the answer Part e) is
[tex]\frac{22}{5}[/tex]
Answer:
Step-by-step explanation:
1. [tex]\frac{-1}{2} + \frac{1}{3}[/tex]
We solve it by taking LCM (-3 + 2) / (3 x 6) = 1/6
2. [tex]-3\frac{1}{5} + (-6\frac{1}{2} )[/tex]
By taking LCM:
-3 1/5 = (-3 x 5 + 1) / 5 = -16/5
-6 1/2 = - (6 x 2 +1) / 2 = -13/2
Subtracting these values:
-16/5 + (-13/2) = -97/10
3. [tex]\frac{5}{8} - (-\frac{2}{8} )[/tex]
Adding the fraction to get: 5/8 + 2/8 = 7/8
4. [tex]-\frac{9}{10} - \frac{2}{5}[/tex]
Taking the LCM:
(-9 - 4) / 10 = 13/10
5. [tex]6\frac{3}{5} - (-2\frac{1}{5} )[/tex]
Taking the LCM to get:
33/5 + 11/5 = 22/5